Comparison of Physicochemical Changes and Water Migration of Acinetobacter johnsonii, Shewanella putrefaciens, and Cocultures From Spoiled Bigeye Tuna (Thunnus obesus) During Cold Storage - Wang, Xin-Yun; Xie, Jing (Frontiers in Microbiology, 2021)
This study investigates the physicochemical changes and water migration of Acinetobacter johnsonii (A), Shewanella putrefaciens (S), and cocultured A. johnsonii and S. putrefaciens (AS) inoculated into bigeye tuna during cold storage. The physicochemical indexes [fluorescence ratio (FR), total volatile base nitrogen (TVB-N), thiobarbituric acid (TBA), trimethylamine (TMA), peroxide value (POV), and pH] of bigeye tuna increased cold storage. A significant decrease in trapped water was found in the AS samples, and direct monitoring of the water dynamics was provided by low-field nuclear magnetic resonance. Samples inoculated with A. johnsonii and S. putrefaciens also induced the degradation of myofibrillar proteins and weakness of some Z-lines and M-lines. Higher values of physicochemical indexes and water dynamics were shown in the coculture of S. putrefaciens and A. johnsonii than in the other groups. Therefore, this paper reveals that the coculture of A. johnsonii and S. putrefaciens resulted in a bigeye tuna that was more easily spoiled when compared to the single culture. This study provides insight into the spoilage potential of A. johnsonii and S. putrefaciens during cold storage, which further assists in the application of appropriate technologies to keep the freshness of aquatic foods.